(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aims to measure the impact of the quality of online news website design—including visual design, usability, content quality, and future usability—on user experience and loyalty in Saudi Arabia. The research followed a descriptive-analytical approach using an online questionnaire administered to a representative sample of 385 internet users in Saudi Arabia, selected via simple random sampling based on the Krejcie and Morgan formula. Data were analyzed using SPSS software, employing statistical techniques such as frequencies, percentages, means, standard deviations, t-tests, and multiple regression analysis. The findings indicated that the quality of news website design significantly and positively affects users’ experience and loyalty. The study recommends enhancing visual design and ease of use to deliver a positive and sustainable user experience that strengthens loyalty toward news websites.